2005
DOI: 10.1159/000083143
|View full text |Cite
|
Sign up to set email alerts
|

Thoracoscopic Decortication: First-Line Therapy for Pediatric Empyema

Abstract: Video-assisted thoracoscopic surgery (VATS) has become a popular and well-refined procedure. It has several advantages over open thoracotomy in terms of invasiveness and cosmetics. The aim of this study is to consider if VATS can serve as primary management for pediatric empyema. Between October 2000 and December 2002, 13 children with empyema receiving VATS were retrospectively reviewed. Of them, 5 had tube thoracostomy before VATS intervention (group T), and 8 had VATS as the initial treatment (group V). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Thoracotomy and to a lesser extent, thoracoscopy are not without significant long-term complications. Whilst some authors have indicated that early thoracoscopy is beneficial, in our own experience we reserve it for those cases that urokinase failed in alleviating the condition [23]. Other centres have used tissue plasminogen activator (tPA) with similar success [24].…”
Section: Discussionmentioning
confidence: 99%
“…Thoracotomy and to a lesser extent, thoracoscopy are not without significant long-term complications. Whilst some authors have indicated that early thoracoscopy is beneficial, in our own experience we reserve it for those cases that urokinase failed in alleviating the condition [23]. Other centres have used tissue plasminogen activator (tPA) with similar success [24].…”
Section: Discussionmentioning
confidence: 99%
“…26 Management strategies have ranged from conservative treatment of parapneumonic empyema 27 to thoracoscopic decortication, the first-line therapy for pediatric empyema. [28][29][30] All patients who needed a CT scan to determine if they had intrapulmonary or extrapulmonary disease had a higher likelihood of needing a thoracoscopy. If thoracoscopy was done within 48 hours of admission, a significantly shorter length of stay was documented.…”
Section: Discussionmentioning
confidence: 99%
“…Six studies, including two randomized trials 37,65 have reported on children treated by VATS in the 2002-2006 time frame and are summarized in Table 2. 37,40,[65][66][67][68] In these studies postoperative chest drainage averaged 2.8 to 5.0 days; hospital stay 5.8 to 8.4 days postprocedure, and success rate (judged as no further surgical procedure) ranged from 83 to 100%. The prolonged operative time and significant blood loss reported in early VATS studies are now rare and operative morbidity is low.…”
Section: Primary Video-assisted Thoracoscopic Surgerymentioning
confidence: 99%